"Disjointed Parts": An Introduction to the SF Short-Shorts of Hoshi Shinichi - Cronin, Caitlin N. (Tufts Archival Research Center, 2005)
A translation of thirteen short stories from Hoshi Shinichi's "Disjointed Parts" collection, featuring an introduction to the author's style and an analysis of themes in the work.